SOSIALISASI MITIGASI SAMPAH LAUT PADA SISWA PRAMUKA PENGGALANG DAN PENEGAK KWARTIR RANTING TELUK AMBON KOTA AMBON - W. Tuahatu, Juliana; A. Noya, Yunita; D. Manuputty, Gratia (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Quarter. However, as residents of coastal areas, students still need to be equipped with basic knowledge about marine debris from the concept of mitigation to the basic methods for waste research. The Community Service Program aims to increase the knowledge of the Scouts of the Ambon Bay Quarter about marine debris mitigation and to train skills in basic waste research methods. The socialization applied lecture and discussion methods, while the training was conducted simulatively in the school environment. The training resulted on waste collection that were dominated by macro size (2.5-100 cm), and categorized into four types, namely paper (19.81%), metal (6.17%), glass (1.82%), and plastic (72.19%). Prior to the activity, the evaluation was carried out; it showed the value of initial knowledge was quite varied, including marine debris mitigation, sources, classification, and waste sorting (0-4%), the impact of marine debris and its sources (4.35%), debris counting (8.70 %), garbage collection (100%). After the activity, the knowledge was significantly increased reaching 95.65%-100% for all indicators. This combination of socialization and training had a positive impact on increasing students' knowledge and skills related to the topic. It is expected that students can implement it in various scouting activities particularly those related to the environment. In addition, as a coastal community, scouts can also be consistence in thinking and working in the coastal and marine environment, now and in the future.